History of Logo - Solomon, Cynthia; Harvey, Brian; Kahn, Ken; Lieberman, Henry; Miller, Mark L.; Minsky, Margaret; Papert, Artemis; Silverman, Brian (Proceedings of ACM on programming languages, 2020)
Logo is more than a programming language. It is a learning environment where children explore mathematical ideas and create projects of their own design. Logo, the first computer language explicitly designed for children, was invented by Seymour Papert, Wallace Feurzeig, Daniel Bobrow, and Cynthia Solomon in 1966 at Bolt, Beranek and Newman, Inc. (BBN). Logo’s design drew upon two theoretical frameworks: Jean Piaget’s constructivism and Marvin Minsky’s artificial intelligence research at MIT. One of Logo’s foundational ideas was that children should have a powerful programming environment. Early Lisp served as a model with its symbolic computation, recursive functions, operations on linked lists, and dynamic scoping of variables. Logo became a symbol for change in elementary mathematics education and in the nature of school itself. The search for harnessing the computer’s potential to provide new ways of teaching and learning became a central focus and guiding principle in the Logo language development as it encompassed a widening scope that included natural language, music, graphics, animation, story telling, turtle geometry, robots, and other physical devices.